A study on zakat education assistance for poor - Aishah Tamby Omar; Nurul Athirah Jamlin; Rasidah Arshad; Rosmah Mat Isa; Sarip Adul (Human Resource Management Academic Research Society (HRMARS), 2022)
Zakat has been acknowledged for its role in establishing social justice and security among the Muslim community to avoid economic inequalities and unfavorable consequences. This study examines the role of zakat education assistance in growing human capital and balanced wealth distribution. Furthermore, educational assistantship such as scholarships, educational institution development, and education enhancement through training, workshops, seminars, and motivation for the poor asnaf student in Sabah has been discussed. Finally, a highlight on the managerial challenges and recommendations for zakat education assistance. Hence, this article will analyze the previous related article to gain an in-depth understanding of the current knowledge and information on the effort of zakat institution in empowering the education among poor asnaf students. The findings show that the zakat institution creates numerous efforts where it creates opportunities for the poor asnaf student to pursue their education in higher education and reduce the wealth gaps among poor Muslim society. The practical implication of this study will enhance the education performance monitoring system for poor asnaf students.